Question

eliminate the arbitrary constant from y= Ae^2x +Be^x + C

83

likes415 views

Maude

4.7

58 Answers

To eliminate the arbitrary constant from the given equation, we need to find the relationship between A, B, and C. We can do this by differentiating the equation with respect to x.

Step 1: Differentiate the equation y = Ae^(2x) + Be^x + C with respect to x.

\begin{align*}

\frac{dy}{dx} &= \frac{d}{dx}(Ae^(2x)) + \frac{d}{dx}(Be^x) + \frac{d}{dx}(C) \

&= 2Ae^(2x) + Be^x + 0 \

\frac{dy}{dx} &= 2Ae^(2x) + Be^x

\end{align*}

Step 2: Now, equate this differentiated equation to zero to find the relationship between A, B, and C.

2Ae^(2x) + Be^x = 0

Step 3: Factor out the common exponential term e^x.

e^x (2Ae^x + B) = 0

Step 4: Since e^x is always positive and never equal to zero, we can set the expression within parentheses equal to zero.

2Ae^x + B = 0

Step 5: Solve this equation for A in terms of B.

2Ae^x = -B

Ae^x = -B/2

A = -\frac{B}{2e^x}

Step 6: Substitute the expression for A back into the original equation y = Ae^(2x) + Be^x + C.

y = (-\frac{B}{2e^x})e^(2x) + Be^x + C

y = -\frac{Be^x}{2} + Be^x + C

Step 7: Simplify the expression by finding a common denominator.

y = \frac{2Be^x - Be^x}{2} + C

y = \frac{Be^x}{2} + C

Answer: The equation without the arbitrary constant is y = \frac{Be^x}{2} + C.

Step 1: Differentiate the equation y = Ae^(2x) + Be^x + C with respect to x.

\begin{align*}

\frac{dy}{dx} &= \frac{d}{dx}(Ae^(2x)) + \frac{d}{dx}(Be^x) + \frac{d}{dx}(C) \

&= 2Ae^(2x) + Be^x + 0 \

\frac{dy}{dx} &= 2Ae^(2x) + Be^x

\end{align*}

Step 2: Now, equate this differentiated equation to zero to find the relationship between A, B, and C.

2Ae^(2x) + Be^x = 0

Step 3: Factor out the common exponential term e^x.

e^x (2Ae^x + B) = 0

Step 4: Since e^x is always positive and never equal to zero, we can set the expression within parentheses equal to zero.

2Ae^x + B = 0

Step 5: Solve this equation for A in terms of B.

2Ae^x = -B

Ae^x = -B/2

A = -\frac{B}{2e^x}

Step 6: Substitute the expression for A back into the original equation y = Ae^(2x) + Be^x + C.

y = (-\frac{B}{2e^x})e^(2x) + Be^x + C

y = -\frac{Be^x}{2} + Be^x + C

Step 7: Simplify the expression by finding a common denominator.

y = \frac{2Be^x - Be^x}{2} + C

y = \frac{Be^x}{2} + C

Answer: The equation without the arbitrary constant is y = \frac{Be^x}{2} + C.

Frequently asked questions (FAQs)

What is the volume of a cone with a radius of 5 inches and a height of 10 inches?

+

Question: Find the exact values of x, where 0 < x < 2π, such that cot x = -√3.

+

Math question: What is the median of the numbers 3, 5, 7, 11, and 15?

+

New questions in Mathematics